2022
DOI: 10.1101/2022.01.23.22269723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early alveolar epithelial cell necrosis is a potential driver of COVID-19-induced acute respiratory distress syndrome

Abstract: Rationale: Acute respiratory distress syndrome (ARDS) with COVID-19 is aggravated by hyperinflammatory responses even after passing the peak of viral load. However, the underlying mechanisms remain unclear. Objectives : Here, we assess whether alveolar epithelial cell necrosis and subsequent releases of damage associated molecular patterns (DAMPs) at an early disease stage aggravate ARDS with COVID-19 Methods: In patients with COVID-19 with and without ARDS and healthy adults, serum levels of the following … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
(182 reference statements)
0
2
0
1
Order By: Relevance
“…SARS-CoV-2 вызывает острый респираторный дистресс-синдром, который характеризуется некрозом альвеолярного эпителия на ранней стадии заболевания. Некроз альвеолярных эпителиальных клеток включает два типа запрограммированного некроза, а именно: некроптоз и пироптоз [32]. Маркеры эпителиального некроза, и в особенности высокоподвижная группа box-1(HMGB-1), выходят в кровь.…”
Section: биогенез Sars-cov-2 в клетке-хозяине влияние вируса на клетк...unclassified
“…SARS-CoV-2 вызывает острый респираторный дистресс-синдром, который характеризуется некрозом альвеолярного эпителия на ранней стадии заболевания. Некроз альвеолярных эпителиальных клеток включает два типа запрограммированного некроза, а именно: некроптоз и пироптоз [32]. Маркеры эпителиального некроза, и в особенности высокоподвижная группа box-1(HMGB-1), выходят в кровь.…”
Section: биогенез Sars-cov-2 в клетке-хозяине влияние вируса на клетк...unclassified
“…Hitherto, changes in concentrations of D-dimer, cardiac troponin I, renal biomarkers, such as serum urea, creatinine and markers of glomerular filtration rate, C-reactive protein (CRP), ferritin, and certain cytokines/chemokines may have a diagnostic value [2][3][4]. Several studies reported that circulating levels of damage associated molecular patterns, such as cytoskeletal keratin-18 (CK18) fragment M30/M65 ratio (an indicator of cell apoptosis in relation to the total cell death), HMGB-1 or mitochondrial DNA may also reflect the severity of COVID-19 patients [5][6][7]. The activity of ADAMTS13 (a disintegrin and metalloprotease with thrombospondin type 1 motif 13), a regulator of von Willebrand factor (VWF) multimer disruption, typically decline with the increasing extent of inflammatory responses [8].…”
Section: Introductionmentioning
confidence: 99%
“…The primary network highlighted the fact that cell death, widely acknowledged as an essential and crucial step in disease pathogenesis (Deshpande and Zou, 2021;Li et al, 2022;Tojo, 2023;Yuan et al, 2023) was not present in any of the AOPs, hence in the network. Therefore, the KE "cell death" KE1825 present in the Wiki was added as a new node connecting "increased coronavirus production" (KE1847 from AOP430) to "increased, secretion of proinflammatory mediators (KE 1496 from AOP392).…”
Section: Identification Of Missing Kes and Emergence Of A New Aopmentioning
confidence: 99%